Laparoscopic repair of a gastric volvulus occurring as a long-term complication of left pneumonectomy: Report of a case - YILDIZELİ, BEDRETTİN; BATIREL, HASAN FEVZİ (SPRINGER, 2007)
Gastric volvulus is an extremely rare late complication of pneumonectomy. We report the case of a 61-year-old man who presented with a 1-year history of progressive intolerance of solids and weight loss 33 years after a left pneumonectomy. Preoperative examinations showed a mesenteroaxial gastric volvulus. We performed a laparoscopic Toupet fundoplication and anterior gastropexy, following which his symptoms disappeared.
Keywords: pneumonectomy; laparoscopy; minimally invasive surgery; surgery; complications; GASTROPEXY; LUNG